GAMBARAN KEJADIAN EKSPULSI PEMAKAIAN KONTRASEPSI IUD (INTRA UTERINE DEVICE) PASCA PARTUM DI PUSKESMAS KEMBARAN 1 TAHUN 2014 - Wachyu Desi Andriyani; Maya Safitri; Susilo Rini (Universitas Harapan Bangsa Purwokerto, 2014)
Intra Uterine Device (IUD) contraception is still little used in family planning programs inIndonesia. IUD have been shown to not increase the risk of infection, perforation and bleeding.However, the incidence of expulsion higher (6-10%). Based on preliminary studies that have beenconducted by researchers at February 25, 2013 in Kembaran I Health Center data obtained fromthe 272 acceptor which uses, 121 IUD acceptors IUD are experiencing expulsion.This study aims to describe the incidence of expulsion of Contraception IUD (Intra Uterine Device)Post-Partum in Regional Kembaran I Health Center at 2014. Methods the study was a retrospective descriptive approach. The sample used is total sampling.The sample was all women who use the contraceptive IUD are 272 acceptors.From these studies showed acceptors were 151 (55.5%) did not undergo expulsion, while theacceptor 72 (62.1%) with parity primiparous, 87 (53.4%) acceptor with a history of serviceJampersal and 81 (50.6 %) acceptor with a history of mounting <40 days experienced expulsion. From these results the authors concluded that most of the acceptors are not experiencingexpulsion, expulsion is experiencing acceptor with parity primiparous, with a history ofservice Jampersal acceptor and acceptor with a history installation <40 days. Finally 272total acceptor IUD acceptors who suffered expulsion of as many as 121 acceptor. Keywords: post partum expulsion, IUD.